2020
DOI: 10.1038/s41598-020-70934-x
|View full text |Cite
|
Sign up to set email alerts
|

Urban food subsidies reduce natural food limitations and reproductive costs for a wetland bird

Abstract: there is a strong conservation need to understand traits of species that adapt to urban environments, but results have been equivocal. Wetland birds exhibit a strong phylogenetic signal towards urban tolerance; however, they have largely been ignored in urban studies. in their historic ranges, wetland birds inhabit dynamic systems, traveling long distances to locate food. this ability to exploit dynamic resources may translate to success in urban environments, areas characterized by novel food opportunities. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 82 publications
2
30
0
Order By: Relevance
“…The implications of feeding primarily on urban vs. natural prey resources on population dynamics of urban adapters are unclear. Though there is no strong consensus, some studies have found that individuals feeding on urban food items have higher reproductive success and greater body condition 52 , 53 , most likely due to the higher caloric density and abundance of urban food. However, other studies have found that reproductive success is lower for urban foragers, potentially due to overall low nutrient concentrations in urban food 54 , 55 .…”
Section: Discussionmentioning
confidence: 99%
“…The implications of feeding primarily on urban vs. natural prey resources on population dynamics of urban adapters are unclear. Though there is no strong consensus, some studies have found that individuals feeding on urban food items have higher reproductive success and greater body condition 52 , 53 , most likely due to the higher caloric density and abundance of urban food. However, other studies have found that reproductive success is lower for urban foragers, potentially due to overall low nutrient concentrations in urban food 54 , 55 .…”
Section: Discussionmentioning
confidence: 99%
“…While the evidence is clear that urbanization can significantly alter biological communities (Fenoglio et al, 2020), in many cases leading to biotic homogenization (McKinney, 2006), there is a large range of responses among species (Gippet et al, 2017; Lintott et al, 2016; Threlfall et al, 2012). Some species have adapted to (Homola et al, 2019), and are even thriving in, urban environments (Evans & Gawlik, 2020), while others have been extirpated by urbanization processes (Warren et al, 2019). In general, species can be placed along a continuum according to their response to urban environments.…”
Section: Introductionmentioning
confidence: 99%
“…Often researchers (sometimes nudged by peer-reviewers) cite this guideline of needing 5 levels before random effects inclusion as a reason why they were unable to use a mixed-effects model (Bain, Johnson & Jones, 2019;Bussmann & Burkhardt-Holm, 2020;Evans & Gawlik, 2020; . CC-BY 4.0 International license available under a was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Discussionmentioning
confidence: 99%